CPFT : uma proposta de processo adaptável para testes funcionais utilizando crowdsourcing - Forno, Mateus Henrique Dal (2016)
The software testing area is became more popular because the software s reliability. There are a few software testing area in the Small business, due a poor the tester labor. This paper presents the construction of a process for performing functional tests through crowdsourcing. The study was developed in four stages: at the first stage, the test approaches study was carried out, as well as the investigation of the use of crowdsourcing for the performance of software test. The second step involved the immersion into a software house, where the Sommerville test process was implemented, identifying the process activities which could be performed via crowdsourcing. The third step involved the process development proposed. The aim was to establish an adaptable structure, one which enables the integration of the process to the software development process used by the organization. In addition, the process is also adaptable regarding the artifacts and the company can adapt them to the equipment which is being used, or replace them by tools or software. The three stages process: Pre-crowd, when the planning and preparation of test cases occur; Crowd, which is responsible for the provision and performance of test tasks and; Post-crowd, which involves the evaluation of the result reported in each test task and evaluation and registration of identified faults. The last stage involved the process evaluation, when it was decided to use the case study approach. The case study is descriptive and integrated, with two analysis units, each one regarding one software house from Passo Fundo city. Fifteen propositions were established, and they were evaluated with the data collected from the performance of the process in each analysis unit. Nine propositions were confirmed, five remain inconclusive and one was refuted. The results show that evinces the feasibility test process proposed, and identifies issues which remain inconclusive